Pengaruh Persepsi Harga dan Promosi Terhadap Keputusan Pembelian Paket Data Internet - Syahla Mutia Aini; Halimah Zahrah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The rapid development of information technology has made the internet an essential need, resulting in increasingly intense competition among mobile data service providers. This study aims to analyze the influence of price perception and promotion on purchasing decisions of Telkomsel internet data packages among students of the Management Study Program, class of 2022, at Universitas Muhammadiyah Bandung. The research employs a quantitative method with a survey approach. The sample consists of students selected using purposive sampling techniques. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS. The findings indicate that price perception has a positive and significant effect on purchasing decisions, while promotion also shows a positive and significant influence. Simultaneously, price perception and promotion significantly affect purchasing decisions, with promotion demonstrating a more dominant influence compared to price perception. The results suggest that well-targeted promotional strategies and appropriate pricing aligned with perceived benefits play a crucial role in enhancing purchasing decisions for Telkomsel internet data packages among university students.